Corporate real estate holding and stock returns: International evidence from listed companies - Joe Cho Yiu Ng; Charles Ka Yui Leung; Suikang Chen (Osaka University, Institute of Social and Economic Research (ISER), 2022)
This study examines the relationship between corporate real estate (CRE) holdings and stock returns before and after the Global Financial Crisis (GFC). We find that (1) the United States and the United Kingdom show a negative relationship before the GFC and positive after the GFC. (2) Firms that pay positive tax or have positive R&D investments are not systematically different from the full sample. This finding cannot support the "scarce capital" theory or the tax incentive explanation, but it is consistent with the "empire building" theory. After the GFC, financial constraints tightened, and both CRE holding and stock returns dropped. (3) European (excluding the United Kingdom) sample shows a positive relationship in the pre-crisis period. This finding is compatible with the "illiquidity premium" theory. However, the association becomes inconclusive in the post-crisis period. (3) The Japanese sample shows a negative association between CRE and stock returns in the pre-crisis period, like the United States and the United Kingdom. However, the relationship becomes statistically insignificant in the post-crisis period, consistent with the theory of financial constraint tightening after the GFC.
Keywords: E44; G10; G30; 330; Global Financial Crisis; corporate real estate holding; collateral constraint; illiquidity premium; panel regression